Epistemological axiology in scientific research practices according to the philosophy of science by Thomas Kuhn - Gómez Navarro, Ángel (2016)
This article starts from the recognition of epistemic valuation standards in scientific researchpractices, both in the stage of normal science and in the stage of scientific revolution according toThomas Kuhn, showing not only relations of axioms, methods and technics, but also relations ofobjectives, interests and values. Intervening epistemic values are classified and studied in orderto set their corresponding justification based on Kuhn’s epistemological considerations, whopresents the values within the context of evaluation and selection of the best scientific theory forthe construction of relevant scientific knowledge.